PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SD NEGERI 183 PEKANBARU - Rohani, Siti; Alpusari, Mahmud; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to improve student learning outcomes in social studies in the subject matter of buying and selling activities within the home and school, with the application of role playing learning model in the third-grade students of SDN 183 Pekanbaru. The low learning outcomes third grade students of SDN 183 Pekanbaru in learning social studies is caused the teacher not applying the appropriate learning model in presenting the material. Making it difficult for students to understand the material presented teachers. The subjects were students of class III student with a numbers are all 38 people consisting of 14 men and 24 women. Parameters measured were the activities of teachers, student activities and student learning outcomes. The data were analyzed descriptively. Results of data analysis obtained by the percentage of the activity of teachers at the first meeting of the first cycle of 75% with the good category, the second meeting of the first cycle of 77.8% with the good category and at the first meeting of the second cycle percentage teacher activity 86.1% with a very good category, the second meeting of the cycle II percentage teacher activity which was 88.9% with very good category. At the first meeting of the percentage of student activity 61.1% with the good category, the second meeting of the first cycle is 77.8% with the good category and at the first meeting of the second cycle the percentage of student activity 80.6% with a very good category, the second meeting of the second cycle, namely 86.1% with very good category. And the score of students in the classical completeness basis is 39.5% (not complete), the first daily test classical completeness of students was 81.6% (completed), and the second daily test classical completeness students was 92.1% (completed). Based on this study concluded that the application of role playing learning model can increase student IPS learning outcomes.Keywords: Role Playing Learning Model, IPS Learning Outcomes